Integrating Religious Moderation Into Fiqh Muamalah Curriculum: An Instructional Development Study - Nurul Mahmudah; Muhammad Syakir Alkautsar; Hamdan Ladiku; Andini Machmud; Muhammad Rifqi Hidayat (Nuban Jagadhita Centre, 2026)
Purpose: This study interrogates the epistemological integration of religious moderation within Fiqh Muamalah instruction, addressing the persistent gap between normative legal formalism and the demands of plural socio-economic realities. While prior studies have treated moderation as an external or complementary discourse. Methodology: To operationalize this claim, the study employs a Research and Development (R&D) design using the ADDIE model to construct and empirically test moderation-based teaching materials in the Islamic Economic Law (HESY) Study Program at IAIN Gorontalo. The empirical phase involved 32 students and 3 lecturers, selected through purposive sampling, alongside expert validators in Fiqh, religious moderation, and instructional design. Findings: The findings demonstrate that embedding the principles of tasamuh (tolerance), tawazun (balance), and ‘adl (justice) within core transactional topics significantly enhances students’ analytical capacity in resolving complex socio-economic cases. Quantitatively, the intervention yielded an average N-gain score of 0.64, indicating moderate effectiveness, alongside a 35% improvement in case-based reasoning performance. Expert validation further confirms the robustness of the developed materials (mean feasibility score: 91%). Theoretically, this study repositions Fiqh Muamalah from a predominantly text-centered and doctrinal paradigm toward a context-responsive legal reasoning framework grounded in maqāṣid al-sharī‘ah. It demonstrates that moderation is not an auxiliary value but a constitutive principle that mediates between legal normativity and social harmony.